Penguatan Pembelajaran Calistung Untuk Penanggulangan Dampak Covid-19 di SD Swasta Masehi Berastagi - Christina Sitepu; Febiola Esrayanti Br Purba; Marisa Yunita Br Depari; Romesli Septima Br Sitanggang; Alda Try Ananda Br Keliat; Salsalina Br Sembiring; Sartika Elvrida Sinaga (Jurnal Pengabdian Masyarakat Formosa, 2022)
Calistung ability is the basic knowledge that must be possessed by someone to be able to learn various things. SD Masehi Berastagi still has problems related to the completion of Calistung's low ability. The purpose of this service is to provide training and assistance to the community at SD Masehi Berastagi in order to be able to improve Calistung's abilities. The service method used is through the stages of observation, socialization, mentoring training, monitoring and evaluation. The implementation of the activity took place in February with the target community of SD Masehi Berastagi students. The results of this service obtained calistung learning media in the form of simple counting tools, picture cards, blackboards, colored pens, and books. The level of student participation in activities is classified as very high, which is indicated by the Calistung ability of the students of SD Masehi Berastagi which has increased after the implementation of the service.